The Malay law text - Mohamad Jajuli A. Rahman (Dewan Bahasa dan Pustaka, Ministry of Education, Malaysia, 1995)
Comments, transliteration, and translation of a law text in Jawi script: MS 2393, Sloane collection, British Museum.